Improving Project Success by Integrating Artificial Intelligence (AI) in Product Development : The Effect of AI Integration on Project Success - Paajaste, Aleksi (My University, 2024)
AI usage has increased significantly in the past few years. Some companies have started to adopt it into their business and some not so much. With this kind of rapidly developing technology there is much potential for new kinds of opportunities and challenges. This thesis looks at the integration of AI to the product development process. The goals were to find what are the pros and cons of integrating AI to product development and what are the results from this. The findings were derived from existing studies on the success factors for product development projects and a study where AI was already deployed within companies. Based on success factors for successful projects AI was found to have many applications that can increase success rates. From the study where AI was already deployed it had had large increases of success due to the integration. From these studies it was found that integrating AI gave businesses potential for higher success rates and lower failure rates. AI can make processes like idea generation, customer inclusion and concept creation more streamlined and efficient. Less mistakes are made when AI is used thus decreasing costs and increasing quality and speed. However, challenges occur concerning building the infrastructure and training staff to use the new tools. Fear of change and the loss of jobs are also challenges to consider.
Keywords: Artificial intelligence, product development, new product development, AI applications, project success